Causal relationship between plasma metabolites and carpal tunnel syndrome risk: evidence from a mendelian randomization study - Wu, Wenbao; Fan, Daofeng; Zheng, Chong; Que, Binfu; Lian, Qing qing; Chen, Yangui; Qiu, Rui (Frontiers in Molecular Biosciences, 2024)
Carpal tunnel syndrome (CTS) is a common symptom of nerve compression and a leading cause of pain and hand dysfunction. However, the underlying biological mechanisms are not fully understood. The aim of this study was to reveal the causal effect of circulating metabolites on susceptibility to CTS.Variance Weighted, MR-Egger, Weighted Median, Simple Mode, and Weighted Model, to examine the association between 1400 metabolites and the risk of developing CTS. We obtained Single-nucleotide polymorphisms (SNPs) associated with 1400 metabolites from the Canadian Longitudinal Study on Aging (CLSA) cohort. CTS data was derived from the FinnGen consortium, which included 11,208 cases and 195,047 controls of European ancestry.The results of the two-sample MR study indicated an association between 77 metabolites (metabolite ratios) and CTS. After false discovery rate (FDR) correction, a strong causal association between glucuronate levels (odd ratio (OR) [95% CI]: 0.98 [0.97-0.99], p FDR= 0.002), adenosine 5'-monophosphate (AMP) to phosphate ratio (OR[95% CI]:0.58 [0.45-0.74], p FDR= 0.009), cysteinylglycine disulfide levels(OR [95% CI] : 0.85 [0.78-0.92], p FDR= 0.047) and CTS was finally identified.In summary, the results of this study suggest that the identified glucuronate, the ratio of AMP to phosphate, and cysteinylglycine disulfide levels can be considered as metabolic biomarkers for CTS screening and prevention in future clinical practice, as well as candidate molecules for future mechanism exploration and drug target selection.